(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2019)
Embelin is a multi targeted therapeutic agent extracted from fruits of Embelia ribes. It exhibits various bioactivities making it a vital molecule of future research. This article focuses on various pharmacological activities involved by Embelin. The plant exhibit extensive pharmacological activities such as wound healing, hypoglycemic, cardiovascular, antioxidant, antimicrobial, antidiabetic and anti fertility.